Economic values for traits of meat sheep in medium to high production potential areas of the tropics - Kosgey, I.S.; Arendonk, Johan A.M. van; Baker, R.L. (Elsevier, 2003)
Breeding objectives were developed for meat sheep in smallholder production circumstances in the tropics. The traits considered were litter size, lambing frequency, pre-weaning, and post-weaning lamb survival to 12 months, ewe survival, lamb live weight at 12-month, mature ewe live weight, consumable meat, kg of manure DM sold per ewe per year and residual DM feed intake. Three evaluation situations were considered: (i) base with constant number of ewes, (ii) fixed feed resource and (iii) setting feed costs to zero. Sensitivity analysis of economic values to price levels of inputs and meat production was carried out. The fixed feed resource situation appropriately describes smallholder production circumstances. In the base situation, meat production accounted for about 88% of revenue and manure the remaining 12%. Variable costs represented about 95% of the total cost. For the fixed feed resource situation, economic values (US$ per ewe per year) were 12.94 for litter size, 10.18 for lambing frequency, 0.19 for pre-weaning lamb survival, 0.24 for post-weaning lamb survival, 0.36 for ewe survival, 1.02 for 12-month lamb live weight, 0.14 for mature ewe live weight, 0.51 for consumable meat, 0.08 for kg of manure DM sold (per ewe per year) and -0.04 for residual DM feed intake. Litter size and lambing frequency were the most important traits in a breeding objective for smallholder production. Relative to the base situation, setting feed costs to zero had similar results as the situation with restricted feed resource but resulted in larger differences. Sensitivity analysis of economic weights to changes in prices and production circumstances indicated that future economic values for traits might change dependent on levels of output and prices. The exceptions, with regard to changes in meat price are kg of manure DM sold per ewe per year and residual DM feed intake, and with regard to feed costs are consumable meat and kg of manure DM sold per ewe per year. Economic values for 12-month lamb live weight, mature ewe live weight, consumable meat, kg of manure DM sold per ewe per year and residual DM feed intake were not sensitive to changes in management and marketing circumstances. Caution is recommended when the breeding objectives presented here are applied not to disadvantage smallholders in poor climatic years, when farmers are at their most vulnerable situation.